The Transnational Mosque: Architecture and Historical Memory in the Contemporary Middle East By Kishwar Rizvi (Chapel Hill: University of North Carolina Press, 2015. 253 pages.) (American Journal of Islam and Society, 2016)
This catchy title, The Transnational Mosque, is timely and implies an analysisof global Islam and the multiplicities of mosque construction today. The premisepromises to contribute to the scholarship on Islamic architecture, and yetthere are some issues with the argument’s structure and even greater ones withthe analytical depth with respect to architecture.The book’s structure highlights the attempt to separate itself and “buildsupon” (p. 7) established texts on the subject of contemporary Islamic architecture.However, its relatively small format, dense with text, is populatedsparely with uneven visual representation. The photographs vary in qualityand vantage, and not all of the mosques discussed have images and architecturaldrawings – serious omissions in a field that is so visual, systematic comparativeanalysis requires analogous efforts with visual representation for theargument to sustain itself. The book contains an introduction; one chaptereach on Turkey, Saudi Arabia, Iran, and the United Arab Emirates (UAE);and an epilogue that serves as a conclusion. But this four-fold argument,which focuses on the patron countries, is flawed because it inherently setsup a hierarchy of influence that situates equally the relatively minimal worksof the UAE with the far-reaching impact of Turkey, Iran, and Saudi Arabia.It also ignores the “transnational” quality of those mosques not patronizedby any of them.The introduction, “Agency of History: The Symbolic Potential for theTransnational Mosque,” begins with an italicized brief first-person narrativethat describes Beirut’s Muhammad al-Amin Mosque followed by a long accountof patronage and political climate. Rizvi promises an interdisciplinaryapproach with field work, architecture and photo documentation, interviewswith architects and patrons in a “study [that] interrogates multiple agents anddiverse agendas behind the construction of transnational mosques” (p. 5). Shedefines “trans” as “beyond and across time of history and spaces of nations,”but nevertheless frames the book in terms of nations ...